2023
DOI: 10.1186/s12939-023-02025-y
|View full text |Cite
|
Sign up to set email alerts
|

Informing efforts beyond tailored promotional campaigns by understanding contextual factors shaping vaccine hesitancy among equity-deserving populations in Canada: an exploratory qualitative study

Lena G. Nascimento,
Ève Dubé,
Kathleen E. Burns
et al.

Abstract: Background Vaccine hesitancy exists on a continuum ranging between complete adherence and complete refusal due to doubts or concerns within a heterogeneous group of individuals. Despite widespread acknowledgement of the contextual factors influencing attitudes and beliefs shaping COVID-19 vaccine hesitancy, qualitative research with equity-deserving groups, accounting for unique lived experiences, remains a gap in the literature. We aim to identify and begin to understand and document the uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The rapid spread of the novel coronavirus prompted all high-resource countries to institute a myriad of prevention and control measures and invest massively in developing, procuring, and distributing vaccines (2). With the increased availability of COVID-19 vaccines, calls for vaccine equity within and among countries emerged (3)(4)(5)(6)(7)(8). Vaccine equity in the context of the COVID-19 pandemic was seen as an imperative to "end this pandemic, restart economies, and begin to tackle the other great challenges of our time" (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid spread of the novel coronavirus prompted all high-resource countries to institute a myriad of prevention and control measures and invest massively in developing, procuring, and distributing vaccines (2). With the increased availability of COVID-19 vaccines, calls for vaccine equity within and among countries emerged (3)(4)(5)(6)(7)(8). Vaccine equity in the context of the COVID-19 pandemic was seen as an imperative to "end this pandemic, restart economies, and begin to tackle the other great challenges of our time" (4).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from high-income countries have shown that vaccine hesitancy and poor access to vaccination services are higher among Black, Indigenous, and other minoritized populations than non-racialized people due to historical and current systemic racism and distrust of the health system (6)(7)(8). In Canada, specifically, an analysis based on the 2020 Canadian Community Health Survey (CCHS), an ongoing yearly cross-sectional survey conducted by Statistics Canada, found that Canadians who self-identify as off-reserve First Nations, Black, or Arab were less likely to have received at least one dose of a COVID -19 vaccine (11).…”
Section: Introductionmentioning
confidence: 99%
“…Challenges with vaccine hesitancy among minority groups do not stem from their innate vulnerabilities, instead the key drivers are socio-economic factors such as social status, access to social goods, housing, employment, and healthcare services [4,5,6]. Within the Canadian context, one key study found that vaccine hesitancy among Black Canadians primarily stemmed from "the denial of their rights and feeling that decisions were being made for members of the Black community and hesitancy related to medical distrust" [3] (p. 9)…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of research to show the linkages between social determinants, COVID-19 infections and racialization. These social determinants places vulnerable ACB individuals a greater risk of disease and psychological stress (3,5,8). In Canada, heavy policing and social distancing rules were enforced on minority groups, particularly within Black communities reinforcing the mistrust within our social and health systems [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation